Device-guided breathing as a possible tool to improve the outcome of exposure therapy - Maartje Cathelijne de Jong; Cornelis Hendrikus Boersma (Mental Illness, 2010)
Exposure therapy is a widely used treatment for patients with post-traumatic stress disorder. It involves reduction of fear through progressive exposure to frightening stimuli in a therapeutic environment. Here we propose a new method designed to improve the effectiveness of exposure therapy. We hypothesized that device-guided breathing during exposure therapy can increase the capability of the patient to undergo effective exposure. The successful application of the method is described for a single patient. Using a device to slow and regularize breathing, the patient was calmed and experienced a greater sense of control and a profound effect of the exposure. The use of the breathing-guiding device is believed to reduce arousal level and excitability of sympathetic “fight-flight” behaviors. The present study suggests that device-guided breathing integrated with exposure therapy may provide a practically feasible and potentially promising non-pharmacological treatment after trauma.